Cerebral Fructose Metabolism as a Potential Mechanism Driving Alzheimer’s Disease - Johnson, Richard J.; Gomez-Pinilla, Fernando; Nagel, Maria; Nakagawa, Takahiko; Rodriguez-Iturbe, Bernardo; Sanchez-Lozada, Laura G.; Tolan, Dean R.; Lanaspa, Miguel A. (Frontiers in Aging Neuroscience, 2020)
The loss of cognitive function in Alzheimer’s disease is pathologically linked with neurofibrillary tangles, amyloid deposition, and loss of neuronal communication. Cerebral insulin resistance and mitochondrial dysfunction have emerged as important contributors to pathologenesis supporting our hypothesis that cerebral fructose metabolism is a key initiating pathway for Alzheimer’s disease. Fructose is unique among nutrients because it activates a survival pathway to protect animals from starvation by lowering energy in cells in association with adenosine monophosphate degradation to uric acid. The fall in energy from fructose metabolism stimulates foraging and food intake while reducing energy and oxygen needs by decreasing mitochondrial function, stimulating glycolysis and inducing insulin resistance. When fructose metabolism is overactivated systemically, such as from excessive fructose intake, this can lead to obesity and diabetes. Herein, we present evidence that Alzheimer’s disease may be driven by overactivation of cerebral fructose metabolism, in which the source of fructose is largely from endogenous production in the brain. Thus, the reduction in mitochondrial energy production is hampered by neuronal glycolysis that is inadequate, resulting in progressive loss of cerebral energy levels required for neurons to remain functional and viable. In essence, we propose that Alzheimer’s disease is a modern disease driven by changes in dietary lifestyle in which fructose can disrupt cerebral metabolism and neuronal function. Management of intracerebral fructose metabolism could provide a novel way to prevent and treat this disease.